ANALISIS POLA KONSUMSI PETANI KARET DESA MANGGALA KECAMATAN PINOH SELATAN KABUPATEN MELAWI - B01107098, AGUS SUPARMAN (Jurnal Curvanomic, 2013)
In this research in taking for my skripsi which entitle " Analysis Pattern Consume Farmer Rubber Countryside Manggala District of Pinoh South Sub-Province Melawi", But. pursuant to title which in taking becoming this research internal issue is how pattern consume rubber farmer in Countryside Manggala District of Pinoh South Sub-Province Melawi. Besides becoming the target of research in this skripsi is to know and analyse responder characteristic and To know earnings of rubber farmer and its consumption pattern. And research methodologies benefit which in taking that is In this elite of used by method is descriptive Method is an method in checking status a group of human being, an obyek, an situation of is condition of, an idea system, nor an event class at a period of/to now directly location tau leisure. Intention of this descriptive research is to make deskipsi, painting or picture systematically, factual and accurate regarding/ hit fact, nature of and also relation/link between phenomenon investigated and relation/link for the billows of the problem of with research aim to know relation/link among/between two variaber or more. In farmer earnings, pattern consume like done/conducted expenditure to fulfill requirement. of family very big especially if to the number of amount of family member with one residence, because more and more consumption pattern which is needed in family, hence is ever greater of done/conducted expenditure storey;level, whereas low earnings. Consumption represent matter which is absolute to be needed by each and everyone for the living on of. In Economics all expenditure besides used for the saving of named by consumption. To society who live in is rural, expenditure consume more done conducted to fulfill elementary requirement from earnings. As for yielded by earnings is month;moon from amount of responder mean equal to Rp 962.500 and is total of mean consume Rp 1.239.024Farmer rubber saving in the form of because thely all farmer can cast aside the rest of earnings which is is obtained. and some of casting aside him/ it in bank. The saving taken or used at the time of certain for example before religion red-letter day. Key Word : consumption pattern , expenditure, earnings of rubber farmer.